Time-dependent rheological behaviour of cemented backfill mixture. Issue 3 (3rd April 2018) - Deng, X. J.; Klein, B.; Zhang, J. X.; Hallbom, D.; de Wit, B.
Abstract: When cemented backfill mixture (CBM) is transported through pipelines from a backfill plant to stopes, it experiences shearing forces over the transport time. In this paper, the effects of solids concentration, binder content, shear rate and curing time on the time-dependent rheological behaviour of CBM were studied. It was found that over long periods of shearing at a constant rate greater than 5 s −1, the shear stress decreased at first and then increased gradually with time. When the shear rate was less than 0.5 s −1, shear stress increased slightly firstly with shearing time, then it started to behave similar to the test with a higher shear rate whose shear stress decreased firstly and then increased. The samples that were sheared at a higher shear rate exhibited a lower apparent viscosity and the higher yield stress CBM samples displayed more pronounced shear-thinning properties. It was also found that for transient flow, increasing the solids concentration and the curing time lead to both a higher initial shear stress ( τ 0 ) and minimum shear stress ( τ min ). When the cement to tailings ratio increased, the τ 0, τ min and final shear stress after shearing for 3600 s ( τ 3600 ) increased at first, and then subsequently decreased. Moreover, changes in the solids concentration profile and the cement hydration property were displayed during the rheological tests.